THE ROLE OF FORENSIC AUDITING IN DETECTING FINANCIAL FRAUD IN COMPANIES: A CASE STUDY OF IRAQI COMPANIES (World Economics and Finance Bulletin, 2023)
The research aims to highlight the impact of forensic auditing on detecting financial fraud. The Beneish model was used to detect fraudulent practices carried out by companies. The model was applied to the financial statements of a research sample consisting of 5 companies listed in the Iraq Stock Exchange, representing different sectors such as insurance, telecommunications, industry, and banking. The research concluded that using the Beneish model helps forensic auditing in detecting fraudulent practices. The research also recommends enhancing the capabilities of forensic auditors and training them on auditing techniques, including the Beneish model